(-4/3)(-9)

Write you answer in simplest form.

3 answers

(-4/3)(-9) = 36/3 = 12
It’s saying it’s incorrect.
4 / 9 – 3 = ?
Write your answer in simplest form.
To solve the expression 4/9 - 3, we need to find a common denominator. The denominator of 4/9 is already 9, so we can leave it as is. To make 3 have a denominator of 9, we multiply it by 9/9, which is equivalent to 1.
So, 4/9 - 3 can be rewritten as (4/9) - (3/1) = (4/9) - (27/9).
Now that both fractions have the same denominator, we subtract the numerators:
(4 - 27)/9 = -23/9.
Therefore, 4/9 - 3 in simplest form is -23/9.